Two new species of phytoseiid mites (Acari: Phytoseiidae) from the State of São Paulo, Brazil - Lofego, Antonio C. [UNESP]; Demite, Peterson R. [UNESP]; Feres, Reinaldo J. F. [UNESP] (Taylor & Francis Ltd, 2011)
Two new species of phytoseiid mites, Amblyseius ica and Typhloseiopsis dorsoreticulatus, from the State of São Paulo, Brazil, are described and illustrated. Amblyseius ica belongs to the americanus species group and dombeyus species subgroup, being the second species of that subgroup. Typhloseiopsis dorsoreticulatus is the first species of the genus Typhloseiopsis recorded outside Central America.
Keywords: Taxonomy; Amblyseius; Typhloseiopsis; rainforest